Comparison of the effects of tualang honey and tibestan in sperm parameters sexual behaviour and hormonal profile among oligospermia males. - Ismail, Shaiful Bahari (Pusat Pengajian Kesihatan, 2015)
Honey is used as a medicine from the ancient to modern folks. In Malaysian population, honey was used as a supplement for men's health since many years although no clear scientific evidence of its benefit. This study aims to evaluate the effectiveness of Tualang honey on sperm parameters, erectile function, hormonal and safety profiles. A randomized control trial was done using Tualang honey (20 gram) and Tribestan (750 mg) over a period of 12 weeks. Sperm parameters including sperm concentration, motility and morphology were analyzed and erectile function was assessed using IIEF-5 questionnaire. Hormonal profile of testosterone, FSH and LH were studied. Safety profile was measured by hematology profile, renal and liver functions besides adverse event reporting. The volunteers were randomized into two groups and the outcomes were analyzed using SPSS version 18. A total of 66 participants were involved. A significant increment of mean sperm concentration (p<0.001), motility (p=0.015) and morphology (p=0.008) were seen in Tualang honey group. In Tribestan group, a significant I increment of mean sperm concentration (p=0.007) and morphology (p=0.009) were seen. No significant different of sperm concentration, motility and morphology were seen in between Tualang honey and Tribestan group and similar results were also seen in erectile function and hormonal profile. All safety profiles were normal and no adverse event was reported. Tualang honey effect among oligospermic males was comparable with Tribestan in improving sperm concentration, motility and morphology. The usage of Tualang honey was also safe with no reported adverse event.